Peran Literasi Digital dalam Peningkatan Kualitas Guru Pendidikan Anak Usia Dini di Indonesia - Sri Elly Yunara (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2022)
Abstrak InggrisTeachers are creators of learning in the educational process. The quality of PAUD teachers in Indonesia when it was still low was indicated by the low teacher UKG results. Based on the UKG results, PAUD teachers in Indonesia are not in accordance with teacher competency standards, both educational qualifications, pedagogical, professional, personal and social competencies. Efforts to improve the quality of teachers should be pursued immediately. The digital literacy movement in education will accelerate the transformation of digital society. By maximizing digital literacy through the use of today's abundant digital technology, PAUD teachers will be able to adapt to the developments and demands of the industrial era 4.0. PAUD teachers will have competence according to standards to carry out their professional duties to prepare the future of their students as a valuable investment in building superior Indonesian human resources.The abundant availability of digital technology makes it easier for teachers to improve the quality of competence through the use of various digital platforms that can be accessed by anyone, anytime throughout Indonesia. So that the acceleration of quality improvement and equity in the quality of PAUD teachers can be realized immediately.Keyword : Digital literacy, quality improvement, PAUD teachers.. Abstrak Indonesia Guru merupakan kreator pembelajaran proses pendidikan. Kualitas guru PAUD di Indonesia saat masih rendah ditunjukkan dengan hasil UKG guru yang rendah. Berdasar hasil UKG guru PAUD di Indonesia belum sesuai dengan standar kompetensi guru baik kualifikasi pendidikan, kompetensi pedagogis, profesional, pribadi dan sosial. Upaya peningkatan kualitas guru harus segera diupayakan. Gerakan literasi digital di bidang pendidikan akan mempercepat transformasi masyarakat digital. Dengan memaksimalkan literasi digital melalui pemanfaatan teknologi digital yang melimpah saat ini, guru PAUD akan sanggup beradaptasi dengan perkembangan dan tuntutan era industri 4.0. Guru PAUD akan memiliki kompetensi sesuai standar untuk melaksanakan tugas profesionalnya menyiapkan masa depan anak didik sebagai investasi berharga membangun sumber daya manusia Indonesia yang unggul.Ketersediaan teknologi digital yang melimpah mempermudah guru meningkatkan kualitas kompetensi melalui pemanfaatan berbagai platform digital yang dapat diakses oleh siapa saja, kapan saja di seluruh wilayah Indonesia. Sehingga percepatan peningkatan mutu dan pemerataan mutu guru PAUD dapat segera terwujud.Kata Kunci: Literasi digital, peningkatan kualitas, guru PAUD.